EXERCISE IN PATIENTS WITH POST OPERATIVE RECONSTRUCTION ACL: A CASE STUDY - Mursyida, Luthfa; Herawati, Isnaini (Universitas Muhammadiyah Surakarta, 2021)
Introduction: The ACL is a break or tear in the ligaments in the knee joint. ACL injuries usually cause functional impairment and instability of the knee. The main problems after ACL injury are deficits or weakness of knee muscle strength, joint instability, and proprioception deficits. The annual incidence of ACL injuries increased by 43% (from 54.0 to 77.4 per 100,000 population), and 74% among those under 25 years of age (from 52.6 to 91.4 per 100,000 population). Injuries are more common in men than women. One of the interventions that can be given is exercise. Exercise is able to reduce the value of pain, activate the muscles in the injured leg, increase knee flexion, and improve the patient's functional ability. Case Presentation: A 20-year-old man came to the clinic complaining of pain, aches, and difficulty in bending his right knee in full ROM. sometimes felt in the morning. In addition, pain increases when walking long distances and going up and down stairs, complaints arise after suffering an injury while playing soccer. Then the patient underwent ACL reconstruction on February 3, 2021 and underwent physiotherapy on February 17, 2021. Management and Outcome: Exercise is one of the physiotherapy management that can be done on post-operative reconstruction ACL patients to reduce pain, activate the muscles in the injured leg, increase knee flexion, and improve the patient's functional ability. Discussion: Patients with postoperative reconstruction usually complain of pain, weakness of the injured leg muscles, difficulty in flexing the knee in full ROM, and others. This study states that exercises in the form of stretching, strengthening, and balance can reduce pain scores, activate the muscles in the injured leg, increase knee flexion, and improve the patient's functional ability. Conclusion: Exercises for postoperative ACL reconstruction patients in the form of stretching, strengthening, and balance can be used as a physiotherapy management for ACL postoperative reconstruction.